ANALISIS DINAMIKA STRUKTUR JEMBATAN RANGKA BAJA UNTUK MENGETAHUI PERILAKU STRUKTUR - Bagus Acung Billahi; Kukuh Wisnuaji Widiatmoko; Faizal Mahmud; Fahrudin Ahmad (Faculty Of Engineering University 17 August 1945 Semarang, 2025)
The old bridge structure, are subjects that must be monitored in bridge maintenance. Bridge detection supervision is very necessary to determine structural deformation caused by normal operations or environmental impacts such as temperature, humidity and heavy vehicle loads. Monitoring the structure as a whole also needs to be carried out after extreme conditions occur, such as an earthquake. Research on structural dynamics analysis of steel frame bridge conditions to determine the behavior of the structure. Vibration data is read using a wireless sensor network or accelerometer. The vibration mode signal obtained is processed using Fast Fourier Transform (FFT) analysis via MATLAB software, which will produce a graph of the relationship between the frequency domain and the time domain. Through this graph, the dynamic characteristics of the bridge structure can be analyzed, with several variations in the condition of the bridge structure.